Further remarks on the deflexion and grammaticalization of the Old English past participle with habban - Martin Arista, Javier (International Journal of English Studies, 2020)
This article deals with the transitive construction involving habban and the past participle in Old English, and focuses on the loss of the adjectival segment of the participial inflection. The analysis is based on data retrieved from the York–Toronto–Helsinki Parsed Corpus of Old English Prose. Inflectional morphology and constituent order, including the relative and the absolute position of the past participle, are considered. The data indicate that the reanalysis the habban+past participle construction is nearly over by the end of the period.